The Relationship between Core Competencies and Critical Thinking with regard to the Moderating Role of Mental Maturity: a study on staff of Rafsanjan University of Medical Sciences - Hasan Jafari ShahrAbadi; Malikeh Beheshtifar; Leila Vali (Kerman University of Medical Sciences, 2017)
Background & Objectives: Core competencies are used to order organizational skills and techonlogies for the purpose of satisfying the customers' needs. Critical thinking and mental maturity help to achieve this goal. The aim of this research was to study the relationship between core competencies and critical thinking with regard to the moderating role of mental maturity in staff of Rafsanjan University of Medical Sciences in 2016. Methods: This descriptive - analyctical study was done on 267 staff of Rafsanjan University of Medical Sciences selected through randomized stratified sampling. Data collection was conducted through using core competencies questionnaire (14 qeustions), critical thinking questionnaire (23 qeustions) and mental maturity questionnaire (19 qeustions). The relationship between variables were analyzed using Partial Least Squares (PLS) and through Smart PLS 2 software. Results: The coefficient between core competencies and critical thinking variables was 11.223 and core competencies directly explained 36 percent of critical thinking variations. But, the coefficient between core competencies and mental maturity variables was 0.993. Therefore, the effect of mental maturity as a moderating variable was not approved. Conclusion: The presence of critical thinking in organization and the opportunity for employees to express their opinions and suggestions lead to the presence of core competencies in organizations and it is possible through gathering, sharing and saving data. Keywords: Core competence, Critical thinking, Mental maturity, Employees Citation: JafarAbadi Shahrabadi H, Beheshtifar M, Vali L. The Relationship between Core Competencies and Critical Thinking with regard to the Moderating Role of Mental Maturity: a study on staff of Rafsanjan University of Medical Sciences. Journal of Health Based Research 2017; 2(4): 395-405.